2022
DOI: 10.1021/acscatal.1c05555
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Initiated Hydrooxygenation of Unactivated Alkenes─A Strategy for Anti-Markovnikov Hydrofunctionalization

Abstract: Hydrofunctionalization of unactivated alkenes is an indispensable mean in synthetic chemistry. Given that addition of electrophilic species into alkenes intrinsically follows the Markovnikov rule, a regioselectivity switch presents a major challenge. Herein, we present a visible-light-promoted strategy for the selective anti-Markovnikov hydrooxygenation of unactivated alkenes. Therefore, an innovative reagent was carefully designed to release a highly reactive and strongly underdeveloped alkoxycarbonyloxyl rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Thus, we anticipated that this redox-neutral, catalytic method would provide access to a diverse range of saturated heterocyclic scaffolds through a single experimental protocol. Similar mechanistic scenarios have been successful in promoting a number of three-component alkene 1,2difunctionalization reactions, including oxyalkylation, 31−33 fluoroalkylation, 34 bisalkylation, 35 hydroesterification, 36,37 oxyamination, 38 and diamination. 39,40 We specifically highlight the work of Chemler and Um, who demonstrated that carbamateappended trifluoroborate salts serve as reagents for the netoxidative synthesis of pyrrolidines from styrenes, 41 and recent work from Ritter and co-workers demonstrated a similar concept of nucleophile-tethered reductive N-centered radical precursors for the synthesis of morpholines and homomorpholines from styrenes (Figure 1B).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Thus, we anticipated that this redox-neutral, catalytic method would provide access to a diverse range of saturated heterocyclic scaffolds through a single experimental protocol. Similar mechanistic scenarios have been successful in promoting a number of three-component alkene 1,2difunctionalization reactions, including oxyalkylation, 31−33 fluoroalkylation, 34 bisalkylation, 35 hydroesterification, 36,37 oxyamination, 38 and diamination. 39,40 We specifically highlight the work of Chemler and Um, who demonstrated that carbamateappended trifluoroborate salts serve as reagents for the netoxidative synthesis of pyrrolidines from styrenes, 41 and recent work from Ritter and co-workers demonstrated a similar concept of nucleophile-tethered reductive N-centered radical precursors for the synthesis of morpholines and homomorpholines from styrenes (Figure 1B).…”
mentioning
confidence: 84%
“…Our reaction design consists of a bifunctional reagent 14 carrying an NHPI ester and a tethered nucleophile, which we hypothesized would pair with an aryl alkene partner through the following sequence of elementary steps (Figure 1D). First, single-electron reduction of the NHPI ester by the excited state 34 bisalkylation, 35 hydroesterification, 36,37 oxyamination, 38 and diamination. 39,40 We specifically highlight the work of Chemler and Um, who demonstrated that carbamateappended trifluoroborate salts serve as reagents for the netoxidative synthesis of pyrrolidines from styrenes, 41 and recent work from Ritter and co-workers demonstrated a similar concept of nucleophile-tethered reductive N-centered radical precursors for the synthesis of morpholines and homomorpholines from styrenes (Figure 1B).…”
mentioning
confidence: 99%
“…Similar mechanistic scenarios have been successful in promoting a number of three-component alkene 1,2difunctionalization reactions, including oxyalkylation, 31,32 fluoroalkylation, 33 bisalkylation, 34 hydroesterification, 35,36 oxyamination, 37 and diamination. 38,39 We specifically highlight the work of Chelmer and coworkers, who demonstrated that carbamate-appended trifluoroborate salts serve as reagents for the net-oxidative synthesis of pyrrolidines from styrenes, 40 and recent work from Ritter and coworkers, who demonstrated a similar concept of nucleophile-tethered reductive N-centered radical precursors for the synthesis of morpholines and homomorpholines from styrenes.…”
mentioning
confidence: 84%
“…Over the decades, N–O activation has been efficiently achieved through visible-light-driven reductive SET of an electrophore, wherein the disparity between the electron densities at the N and O heteroatoms due to the presence of unique functional groups is exploited to selectively generate either (i) an O-centered radical (O • ) and N – from N electrophores or (ii) a N-centered radical (N • ) and O – from O electrophores (Figure a). N -Alkoxypyridinium salts, N -(acyloxy)­phthalimides, and thiohydroxamic esters act as N electrophores, whereas O electrophores consist of oxime derivatives, N -(acyloxy)­phthalimides, , N , O -disulfonyl- N -alkylhydroxylamines, , N -oxyamines, N -oxyamides, N -oxycarbamates, and dioxazolones . The weakening of the N–O bond after SET reduction eventually results thermodynamically favored defragmentation.…”
Section: N–o Bond Activation By Photoredox Catalysismentioning
confidence: 99%